2016
DOI: 10.1071/rd15354
|View full text |Cite
|
Sign up to set email alerts
|

Fertility and genomics: comparison of gene expression in contrasting reproductive tissues of female cattle

Abstract: To compare gene expression among bovine tissues, large bovine RNA-seq datasets were used, comprising 280 samples from 10 different bovine tissues (uterine endometrium, granulosa cells, theca cells, cervix, embryos, leucocytes, liver, hypothalamus, pituitary, muscle) and generating 260 Gbases of data. Twin approaches were used: an information-theoretic analysis of the existing annotated transcriptome to identify the most tissue-specific genes and a de-novo transcriptome annotation to evaluate general features o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 53 publications
1
7
0
1
Order By: Relevance
“…In summary, the HPLC-based characterization of cervical mucins revealed the presence of oligoSia chains and verified the results of the polySiaT activity assay demonstrating that bovine cervical mucins can be used as an acceptor for bacterial polySiaT. Interestingly, expression data from bovine cervix and uterus already demonstrated that mRNA of different a2,8-sialyltransferases are present in the female reproductive tract [37,38]. However, until now it is not known, which mammalian a2,8-sialyltransferase can use glycans on mucins as an acceptor.…”
Section: Characterization Of the Oligosialylation Status Of Bovine Cesupporting
confidence: 67%
“…In summary, the HPLC-based characterization of cervical mucins revealed the presence of oligoSia chains and verified the results of the polySiaT activity assay demonstrating that bovine cervical mucins can be used as an acceptor for bacterial polySiaT. Interestingly, expression data from bovine cervix and uterus already demonstrated that mRNA of different a2,8-sialyltransferases are present in the female reproductive tract [37,38]. However, until now it is not known, which mammalian a2,8-sialyltransferase can use glycans on mucins as an acceptor.…”
Section: Characterization Of the Oligosialylation Status Of Bovine Cesupporting
confidence: 67%
“…To confirm "typical" hypothalamic gene expression from this list of expressed genes is challenging. A recent study of female cattle tissues found that less than 1% of annotated genes presented a restricted tissue-specific expression (McGettigan et al, 2016). The 10 most hypothalamicspecific genes, according to McGettigan et al (2016), were expressed in all our samples (RPKM > 0.2 in each ◊ sample) and did not differ between postpubertal and prepubertal heifers.…”
Section: Resultsmentioning
confidence: 59%
“…A recent study of female cattle tissues found that less than 1% of annotated genes presented a restricted tissue-specific expression (McGettigan et al, 2016). The 10 most hypothalamicspecific genes, according to McGettigan et al (2016), were expressed in all our samples (RPKM > 0.2 in each ◊ sample) and did not differ between postpubertal and prepubertal heifers. These 10 genes, including the most specific myelin proteolipid protein, might be considered constitutively expressed in the hypothalamus because they could be confirmed by others and were independent of developmental status in our samples (P > 0.05).…”
Section: Resultsmentioning
confidence: 59%
“…6/8 Encontrar la expresión de genes asociados a la unión, está de acuerdo con la naturaleza fisiológica de los folículos que en ese tamaño son un tejido proliferativo que para su desarrollo necesita una gran cantidad de RNA mensajeros de señales (18) para cumplir su función: inmediata de ovulación e indirectamente un oocito competente para formar un embrión. Otros trabajos donde hay comparación de expresión diferencial en folículos informan que existen en los búfalos 110 genes diferencialmente expresados pertenecientes a 14 vías metabólicas y que para las vacas se encontraron 446 genes que pertenecían a 10 vías metabólicas (14).…”
Section: Discusionunclassified